Three Interpretation Paths on Understanding Political Relations between Southeast Asian Kingdoms and China from the Mandala System’s Perspective - Zhao, Qidong (Pacific International Journal, 2024)
In the late 1960s, some scholars started using the constituent elements of the mandala system, the traditional interstate relations model in Southeast Asia, to explore the official relationship between China and Southeast Asian Kingdoms and gradually formed three interpretation paths. The first is to use the mandala in the geopolitical sense to locate bilateral political relations. The second is about how the political culture with the universal monarch as the core enables Southeast Asia monarchs to join the tribute system. The third focuses on the different understanding of tribute in Southeast Asian countries. They supplement or revise the traditional view that the tributary relationship between ancient China and Southeast Asian Kingdoms was political. However, these three interpretation paths have their limitations. The review shows that scholars ignore the universal kingship of Southeast Asian Kingdoms’ discourse system to China. The unilateral policy design and understanding could not convincingly interpret the unique political relationship formed by bilateral interaction. Therefore, the universal kingship claimed by the Chinese emperors and Southeast Asian Kingdoms monarchs must be examined. It should study how the centers of the mandala system smoothly transited between claiming universal kingship and pursuing equality in real politics. It also explores what diplomatic strategies could maintain the subjectivity of the monarchs of Chinese dynasties and Southeast Asian Kingdoms.